Coronary Artery Bypass Grafting Versus Percutaneous Coronary Intervention in Patients With Left Ventricular Systolic Dysfunction: A Meta-Analysis. (January 2017) - Zhang, Dongfeng; Lyu, Shuzheng; Song, Xiantao; Yuan, Fei; Xu, Feng; Zhang, Min; Zhang, Mingduo
The optimal method of coronary revascularization for patients with coronary artery disease (CAD) and left ventricular (LV) systolic dysfunction is unclear. The purpose of this meta-analysis was to compare coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in these patients. Two investigators independently searched PubMed, EMBASE, and the Cochrane Controlled Trials Register databases for relevant studies. Four prospective and 5 retrospective studies, published before March 2015, involving 6082 patients were included. Compared with PCI, CABG was significantly associated with lower long-term death (odds ratio [OR]: 0.82, 95% confidence interval [CI]: 0.70-0.96, P = .01, I 2 = 0%), myocardial infarction (OR: 0.58, 95% CI: 0.36-0.95, P = .03, I 2 = 44%), and repeat revascularization (OR: 0.17, 95% CI: 0.14-0.22, P < .001, I 2 = 32%). The short-term death rate was comparable between CABG and PCI (OR: 2.09, 95% CI: 0.80-5.45, P = .13, I 2 = 9%). Coronary artery bypass grafting has long-term benefits compared with PCI in patients with CAD and LV dysfunction.